FAKTOR-FAKTOR YANG MEMENGARUHI EXCESSIVE DAYTIME SLEEPINESS PADA MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS KATOLIK INDONESIA ATMA JAYA - Clarisa Seravine; Nawanto Agung Prastowo (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: Excessive daytime sleepiness is a person's tendency to fall asleep when they should be awake. This can cause various problems in the performance of daily activities such as a decrease in workplace productivity, traffic accidents, and a lower academic score among medical students. Therefore, this study was conducted to determine the factors that influence the occurrence of excessive daytime sleepiness among the students of Atma Jaya Catholic University of Indonesia School of Medicine dan Health Sciences (FKIK UAJ).Methods: This research is a descriptive analytic study with a cross-sectional approach on respondents consisting of preclinical students from the year 2015 -2017. Respondents were given questionnaires containing demographic data, Epworth Sleepiness Scale (ESS), and subjective sleep duration. Data on height, weight, and waist circumference of the respondents were taken using their corresponding measuring instruments. The analysis was conducted using logistic regression in order to find which factors has the most influence on excessive daytime sleepiness.Results: In this study, 132 students from FKIK UAJ who met the inclusion criteria were were selected as respondents. Data analysis showed that excess body mass index was the most statistically significant factor in the occurrence of excessive daytime sleepiness among FKIK UAJ students with an OR of 14,584 (95% CI 5,651-37,637) followed by inadequate sleep duration with an OR of 3.693 (95% CI 1,183-11,533).Conclusion: This research has found that the greatest factors on the occurrence of excessive daytime sleepiness on the students of FKIK UAJ are excessive body mass index and inadequate sleep duration.